Anatomic variations of the cystic artery in a Colombian cadaveric series. - Quijano-Blanco, Yobany; Camilo Muñoz-Castaño, Ivan (Revista Facultad de Medicina de la Universidad Nacional de Colombia, 2025)
Introduction: Compared to other countries, studies on the anatomical characteristics of the cystic artery in the Colombian population are scarce. Objective: To describe the anatomical characteristics of the cystic artery in a sample of 60 cadaveric specimens from Colombia. Materials and methods: Descriptive study conducted between 2021 and 2023. The cystic artery from 60 digestive tracts of cadaveric specimens with no history of biliary tract disease or surgery was dissected. A macroscopic examination of the cystic artery was performed, and information on its origin, anatomical shape, length, diameter, general anatomical distribution, distribution in relation to the gallbladder, and distribution in relation to the right and left hepatic ducts was recorded. Results: In 95%, 98.33%, and 66.67% of digestive systems, the cystic artery originated in the right hepatic artery, had a linear shape, and extended through the cystohepatic triangle, respectively. Moreover, its mean length and diameter were 15.90±7.36 mm (maximum: 54.10 mm; minimum: 4 mm) and 1.64±2.30 mm (maximum: 9.60; minimum: 2.20 mm), respectively. Conclusions: The characteristics of the cystic artery in a cadaveric sample from the Colombian population are similar to those reported in other countries in terms of origin and length; however, the diameter is smaller.